Drag po raṅ ʼbyuṅ raṅ śar chen poʼi rgyud daṅ Bkaʼ brgyad kyi bsñen thabs ʼdas paʼi źal luñ sogs bcas : a collection [of] Byaṅ-gter texts - Rgod-kyi-ldem-ʼphru-can, Gter-ston, 1337-1408 (Tashi Dorji ; distributor, Tibetan Bonpo Monastic Centre, 1975)
Collection of rare texts of the Changter tradition of Nyingmapa Lamaism.